Ta’līm al-‘Adad biṭ-Ṭarīqah al-Istiqrāiyyah bi Istikhdām Kitab “al-Qawā’id at-Taṭbīqiyyah fī al-Lugah al-‘Arabiyyah bi Ma’had at-Taqwā bi Atsyiyah asy-Syamāliyah - Kasyful Anwar; Aan Muhammady; Danil Zulhendra (Jurnal Sosial Humaniora Sigli, 2023)
Nahwu science is the science of knowing the final state of a sentence in Arabic from the I'rab and bina perspectives. Understanding nahwu science is very important for anyone who wants to write and speak Arabic. There are three elements that influence someone to master Arabic, namely mufradat (vocabulary), Ashwat (sound) and Tarkib (structure). As for number material or in Arabic it is called 'Adad' which is one of several structures in nahwu science in terms of 'Tarkib or arrangement. The problem experienced by second-grade students at the at-Taqwa Islamic Boarding School is their inability to master number material. Therefore, it is expected that all teachers who teach nahwu lessons will use an appropriate method or book to make it easier for them to teach nahwu, namely the book “al-Qawa’id at-Taṭbiqiyyah fi al-Lugah al-‘Arabiyyah” which was compiled using the inductive. The purpose of this study was to determine the effectiveness of the book "al-Qawa'id at-Tathbiqiyyah Fi al-Lughah al-Arabiyyah" in improving students' ability to deal with numbers. This study uses the Quasi Experiment Method, namely without using a control class. Researchers took a sample of 24 students in one class, namely class II-a at the North Aceh At-Taqwa Islamic Boarding School. The instrument used is a test (Pre test-Post test). While the research results show that the use of the book " al-Qawa’id at-Taṭbiqiyyah fi al-Lugah al-‘Arabiyyah " with the inductive method in improving students' ability to matter effective numbers. This can be seen in the results of the T test which are greater than the results of the Ttable test.